Crip Linguistics Goes to School - Jon Henner; Octavian Robinson (Languages, 2023)
Teachers of the deaf, signed language interpreters, and associated staff (e.g., secretaries and sanitation workers) are a salient part of a deaf child’s community often because hearing parents and other family members of deaf children do not become proficient signers leading many deaf children and adults to feel alienated in the home environment (e.g., dinner table syndrome). Because the school environment provides another way for deaf children to acquire language, professional signed language fluency is critical. Yet, in other second language acquisition contexts, fluency is not necessary for effective teaching and often highly racialized. If perceived fluency is often dependent on proximity to whiteness, and language fluency is not necessary for effective teaching, then why is it necessary to require professionals to be fluent in signed languages before teaching and working with deaf children?